Knowledge and practices of community pharmacists in topical dermatological treatments - Teixeira, Ana (2021)
The connection between pharmacists’ knowledge and practice on the provided information to patients about dermatoses and their treatment is insufficiently characterized. Furthermore, pharmacists’ contributions in counselling and in promoting adherence to topical treatment is not fully understood. This study has three main objectives. It aims to identify the knowledge and practices of pharmacists about dermatoses and their treatment, and to compare the perspective of pharmacists with that of patients regarding treatment information, with the future goal of establishing guidelines on the communication of dosage regimen instructions to dermatological patients and promotion of adherence to treatment, filling a gap. A cross-sectional, exploratory, and descriptive study was carried out. Based on experts’ prior knowledge and extensive collected literature information, two questionnaire protocols, one for pharmacists and another one for patients, were designed. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were carried out in relation to the pharmacists’ questionnaire for instrument validation. The results indicate that knowledge of pharmacists regarding dermatoses and their treatment is considered acceptable. Most of the pharmacists were reported to provide information to patients. Oppositely, patients reported not to have receive it. This is an important issue because pharmacists play a primary role in the management of several diseases. As non-adherence can be triggered by poor understanding of the dosing instructions, pharmacists’ communication practices play an important role in improving this hinderance. Results from this study identified pharmacist–patient communication gaps, so the development of guidelines to improve the transmission of clear dosage regimen instructions and knowledge about patient’s disease are of paramount importance. Training programs for continuous education of pharmacist should be implemented to solve the identified communication problems found in this study.